2015
DOI: 10.1007/s10654-015-0038-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic exposure in the first year of life and later treated asthma, a population based birth cohort study of 143,000 children

Abstract: Several epidemiological studies reported an association between antibiotic consumption in the first year of life and later asthma, but results are conflicting and affected by potential biases. We examined this controversial issue in a population-based birth cohort. Using administrative data, we identified 143,163 children born in 1995-2011 in Friuli-Venezia Giulia (Italy) (median follow-up 5.25 years, 927,350 person-years). Antibiotic prescriptions in the first year of life and subsequent treated asthma (defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 32 publications
3
50
1
3
Order By: Relevance
“…Therefore, it should be tested in different settings before being considered the gold standard for pediatric asthma detection using healthcare databases in Italy or elsewhere. Anyhow, our previous [2] and present results consistently show an association between early antibiotic use and later pediatric treated asthma across a wide range of asthma definitions.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, it should be tested in different settings before being considered the gold standard for pediatric asthma detection using healthcare databases in Italy or elsewhere. Anyhow, our previous [2] and present results consistently show an association between early antibiotic use and later pediatric treated asthma across a wide range of asthma definitions.…”
supporting
confidence: 83%
“…As suggested by Bianchi et al [1], we have conducted a sensitivity analysis of our previously published data [2], identifying treated asthmatics as those individuals with at least one prescription after the first year of life of any nonnebulised formulation of inhalatory anti-asthmatic drugs [3] Since nebulised formulations of anti-asthmatic drugs are frequently prescribed for respiratory infections [1], our previous definition may have misclassified as asthmatics a proportion of non-asthmatic subjects particularly in the 13-71 months groups and might have biased our results: children treated with antibiotics in the first year of life may be more predisposed to respiratory infections in early childhood; alternatively, antibiotic use may be a marker of parental tendency to seek medications for children.…”
mentioning
confidence: 99%
“…Antibiotics during the first year of life are associated with an increased risk for wheezing and asthma up to the age of three and six years, independent of lower respiratory tract infections during the first year of life. [24][25][26][27][28] The strength of the association differs with the class of antibiotics, correlating with their effect on the gastrointestinal microbiome. 24 A dose-response effect was observed: when five or more antibiotic courses were administered, the risk to develop asthma increased significantly (p<001).…”
Section: Antibiotics and The Respiratory Tractmentioning
confidence: 99%
“…In the absence of effective antiviral therapies, targeting pathogenic bacteria for manipulating the microbiome by antibiotics may be an alternative approach. In contrast, several epidemiological studies reported that antibiotic consumption in the first year of life was associated with a risk of asthma in later life (6,94). Due to the 'common mucosal response' concept, which introduces the idea that the alterations in immune function of the respiratory tract are linked to the immunomodulatory activity of the gut microbiome, oral administration of probiotics was used for treating allergic airway diseases by changing the gut microbiome.…”
Section: Perspectivesmentioning
confidence: 99%